Participation Behavior of East German Women after German Unification - Holger Bonin; Rob Euwals (Institute for the Study of Labor (IZA), 2001)
The paper studies the determinants of labor force participation by East German women after unification. To isolate the role of preferences on labor force participation from individual characteristics, we develop a panel data model that simultaneously explains participation, employment and wages. The model, estimated for East and West Germany on the basis of the German Socio-Economic Panel, indicates that distinct preferences could explain the regional difference in participation rates at unification. Afterward East German women became less willing to participate, but the negative labor supply trend was offset on the aggregate level by changes in characteristics and wages promoting participation.
Keywords: C33; J21; J31; 330; Transitional economies; labor force participation; panel data; Frauenerwerbstätigkeit; Arbeitsangebot; Neue Bundesländer; Nationale Einheit; Deutschland